Social Condition of Fishermen Community in Sungai Apit Subdistrict Due to Social Manipulation for COVID 19 Pandemic - Rindi Metalisa; Fanny Septya; Darwis AN; Tomi Ramadona (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
The COVID 19 pandemic creates a new pattern of life not only in the health aspect, but also in the socio aspects of society with various social engineering as a form of non-natural disasters mitigation. The fishing community is one of the communities affected by the COVID 19 pandemic due to the social engineering of physical distancing which reduces the social space for the fishing community in their daily activities in Sungai Apit District. This study aims to describe the socio conditions of the fisheries community in Sungai Apit District before and during the COVID 19 pandemic due to social engineering. This research was conducted using qualitative methods with purposive sampling technique as many as 18 respondents. This research was analyzed by qualitative descriptive, namely explaining socio phenomena based on qualitative data. The results showed that fishing communities there has been a change due to social engineering on social indicators. Social indicators are the involvement of fishing communities in social institutions, limited social interaction,and changes in health status.